Winning hearts and votes: social services and the Islamist political advantage - Brooke, Steven (Cornell University Press, 2019)
"Based on an investigation of the Egyptian Muslim Brotherhood, the author shows how social services drive electoral support by affiliating the provider organization with the politically valuable traits of competence, compassion, and honesty"--